PERBEDAAN PEMBERIAN TEPUNG ROTI AFKIR TERHADAP PRODUKTIVITAS AYAM PETELUR FASE PRODUKSI - Irvan Jalu Hayuda; Nita opi Ari Kustanti; Resti Yuliana Rahmawati (AVES: Jurnal Ilmu Peternakan, 2022)
The purpose of this study was to determine the difference in giving rejected bread flour to the productivity of laying hens in the production phase in UD. Podo Trisno Farm. The materials were using 200 laying hens in production phase with Lohmann strain, 28 weeks of age. Completely randomized design was used in this research with five treatments and four replications. The treatments were P0 (100% of control feed), P1 (90% feed + 10% rejected bread flour), P2 (85% feed + 15% rejected bread flour), P3 (80% feed + 20% rejected bread flour ) and P4 (75% feed + 25% rejected bread flour). The research variables were daily egg production or Hen Day Production (HDP) and Feed Conversion Ratio (FCR). Data were analyzed by analysis of variance (ANOVA), if there were significant different would be continued with Duncan Multiple Range Test (DMRT). The results showed that the effect of each treatment on HDP and FCR was significantly different (P<0.05). P0 is the best treatment. From the results of the Duncan Multiple Range Test, P0 and P3 were not significantly different on HDP and FCR. P1 and P4 were not significantly different, but different from P3 and P0. P2 is the treatment with the lowest HDP level and the highest FCR 2. So, it can be concluded that the difference in giving rejected bread flour does not affect the Hen Day Production and Feed Convertion Ratio of laying hens in the production phase.